Soil pH for Nutrient Availability and Crop Performance - Oshunsanya, Suarau (IntechOpen, 2019)
This book offers effective methods of regulating soil pH for sustainable crop production by decreasing soil contaminants, balancing soil pH, improving nutrient uptake, and increasing crop yields. The book discusses methods of measuring soil pH, factors influencing soil pH, the influence of soil pH on nutrient availability and microbial activity, the causes and amendments of soil acidity, the effects of fertilizers on soil acidity, and soil pH preferences of various crops. This book will serve as a guide for understanding the roles of pH in soil and crop productivities. This is an important resource for soil, crop, and environmental scientists, agronomists, crop physiologists, botanists, foresters, wildlife scientists, and students in these disciplines.